Selective excitation of one among the three peaks of tip‐enhanced Raman spectroscopy by a shaped ultrafast laser pulse. (21st December 2019) - Xia, Yingjie; Zhao, Hua; Zhang, Shian; Feng, Donghai; Sun, Zhenrong; Li, Jinping; Jia, Tianqing
Abstract: There are generally several neighboring Raman peaks that are excited simultaneously in tip‐enhanced Raman spectroscopy (TERS). A method to selectively excite a specific Raman peak and simultaneously depress the others is required for suppressing noise and improving detection sensitivity and accuracy. In this study, we demonstrate a scheme for selective excitation of one Raman peak among three excited states in TERS by properly shaping the pump and Stokes femtosecond laser pulses. The shaped pump and Stokes pulses are transformed into time domain, discretized and reconstructed; they are then used to irradiate the TERS structure obliquely. The impulse responses at five probe points of the TERS structure are calculated followed by a Fourier transform. In these cases, the probability of one selectively excited Raman transition increases by several hundreds to tens of thousands in amplitude, whereas the others are both depressed to zero. The probe points at different positions in the tip apex do not affect the enhanced and selective excitation of one Raman transition among the three excited states. Abstract : A scheme is demonstrated for selective excitation of one Raman peak among three excited states in TERS by properly shaping the pump and Stokes femtosecond laser pulses. The impulse response of the TERS structure is calculated. The probability of one selectively excited Raman transition increases by several hundred in amplitude, whereas the other two are both depressed to zero. The enhancement and selection of one Raman transition among the three excited states occur simultaneously in the TERS nanostructure.